Investigation of Membrane Chemical Degradation as a Function of Catalyst Platinum Loading. Issue 6 (4th June 2021) - Spears, André J.; Rockward, Tommy; Mukundan, Rangachary; Garzon, Fernando
Abstract : Membrane chemical degradation is one of many factors that can impact fuel cell durability. The fuel cell's lifetime heavily depends on the membrane and its ability to maintain chemical and mechanical integrity. Previous studies indicate that chemical degradation is due to the formation of hydroxyl radicals that attack the polymer structure resulting in membrane thinning, pinhole formation, and the release of fluoride and sulfate ions. Membrane durability was investigated using ultra-low Pt electrode loadings (≤ 0.1 mgPt cm −2 ). Accelerated stress testing (US-DOE protocols) demonstrated that the degradation rate was found to increase with higher Pt loadings. This is most likely due to more heterogeneous sites for radical formation due to hydrogen crossover to the cathode. We also explored membrane degradation rates while varying catalyst layer thickness, ionomer to carbon ratio, and types of carbon support. All of the aforementioned variables impact the membrane degradation rates.